Flood risk of lower silesia voivodship = Zagrożenie powodziowe województwa dolnośląskiego - Adynkiewicz-Piragas, Mariusz; Lejcuś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Floods are natural events of a random nature that cause damage in property, agriculture, and industry. Floods in the upper and middle Odra basin, particularly on a large scale, are characterized by their specificity of arising and shaping. Analyses of historical material prove that the largest floods are during the summer season, especially in July and August. Those events are caused by wide and intensive precipitation lasting 2-3 days.
Keywords: zlewnia Odry; zagrożenie powodziowe; potencjał powodziowy; flood risk zones; Odra catchment